Strategi pengembangan pasar internasional bagi lembaga keuangan syariah: Analisis faktor pendorong dan penghambat - Naj’la, Ummu (Maliki Interdisciplinary Journal, 2025)
This article aims to analyze international market development strategies for Islamic financial institutions, focusing on driving and inhibiting factors. This research uses a qualitative approach based on secondary data analysis from three related journals. The results indicate that sukuk, as an Islamic financing instrument, has significant potential to support international expansion. Furthermore, halal commodities such as bird’s nests also present significant opportunities to increase the competitiveness of local products in the global market. However, challenges such as a lack of professional human resources, inadequate regulations, and limited Islamic financial infrastructure remain major obstacles. This article recommends strategic steps such as strengthening inter-institutional cooperation, training human resources, and socializing the benefits of Islamic financial institutions to the global community.